THE IMPACT OF THE EXISTENCE OF THE TAKALAR SUGAR FACTORY IN CREATING BUSINESS OPPORTUNITIES IN THE COMMUNITY OF EAST POLONGBANGKENG DISTRICT, TAKALAR REGENCY - Agus Syam; Aprianti Aprianti; Nur Halim; Muhammad Jufri; Sudarmi Sudarmi (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The study's main goal is to thoroughly investigate how the Takalar Sugar Factory impacts the creation of business opportunities within the community, as well as to assess the implementation of Corporate Social Responsibility (CSR) from the community's perspective. The research employs a descriptive qualitative approach, gathering data through observation, interviews, and documentation of a research object. The data will then be analyzed by conducting conclusive interviews with both the community and the factory's workforce, drawing conclusions based on past and present conditions. The findings from the research on the community and the factory's workforce reveal that opening grocery and culinary stalls presents the most promising opportunity to boost community income. This is especially beneficial for workers, as evidenced by the implementation of CSR programs. However, some individuals are unaware of these programs due to insufficient company outreach regarding CSR initiatives and potential business opportunities. The sugar cane crop produced by the factory has a daily milling production target, requiring extensive networks for quick consumer marketing. This presents an opportunity for the community to participate in sugar distribution to consumers.